2016
DOI: 10.1007/s10796-016-9673-7
|View full text |Cite
|
Sign up to set email alerts
|

Delivering public value through open government data initiatives in a Smart City context

Abstract: By using ICT in an innovative way, governments can improve the delivery of services and interaction with stakeholders. Open data is a way to help public organizations became more open and improve interaction with stakeholders. This paper aims to identify what are the public values enhancements acquired on smart city environment that discloses open data. We propose a conceptual model to analyze the smart city initiative. We contextualized the model taking a smart city domain by analyzing three related-initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(113 citation statements)
references
References 50 publications
0
104
0
9
Order By: Relevance
“…The widespread use of information technologies also enables cities to empower the advancement of indispensable services for safety, health, governance and delivery (Hernández-Muñoz et al 2011;Pereira et al 2017). For assisting policymakers on smart city network design, the California Institute for Smart Communities explored ways of transforming a city into smart city along with the extent of utilisation of information technologies in smart city context (Alawadhi et al 2012;Albino et al 2015).…”
Section: Smart Cities Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread use of information technologies also enables cities to empower the advancement of indispensable services for safety, health, governance and delivery (Hernández-Muñoz et al 2011;Pereira et al 2017). For assisting policymakers on smart city network design, the California Institute for Smart Communities explored ways of transforming a city into smart city along with the extent of utilisation of information technologies in smart city context (Alawadhi et al 2012;Albino et al 2015).…”
Section: Smart Cities Developmentmentioning
confidence: 99%
“…Santana et al (2017) suggested that policy planners should address the issues related to data quality and its scalability in smart city context. Janssen et al (2017) and Pereira et al (2017) revealed in their research that big open data initiatives can help in providing real-time weather forecast, pollution and traffic management, creating transparency, better decision and policy-making and crisis management etc., and contribute to enhance the delivery of public value in smart city contexts. Social (SOC) category of barriers occupies next place in the main priority list.…”
Section: Gov) -Economic (Eco) -Technology (Tech) -Social (Soc) -Envirmentioning
confidence: 99%
“…In Table 1 most of the factors are structural factors and only some focus on the process. In this special issue Viale Pereira et al (2017) investigate the process of value creation in smart cities and show that the drivers are diverse and important. In addition, cultural factors, like a risk-averse culture, influence the innovation process.…”
Section: Factors Influencing Data-driven Innovationmentioning
confidence: 99%
“…Thus, the frequency of this specific keyword might be an indication that there might be a core of specific subjects characterizing smart cities research in the scope of e-government. Indeed, Pereira et al (2017), for example, defended that open data initiatives contribute to enhance the delivery of public value in smart city contexts.…”
Section: Most Frequent Abstractmentioning
confidence: 99%